Laparoscopic cholecystectomy, a three-incision approach and one visible scar - Vera Freundt, Mario Guillermo (2012)
Introduction: A gallbladder laparoscopic surgical technique using three separated ports is described, aiming to achieve better esthetic results together with the best clinical outcome, leaving only a 5-mm scar and exclusively requiring standard equipment. Objective: To assess the feasibility of this new surgical technique, pointing out its advantages and limitations. Material and Method: Patients with gallstones or gallbladder polyps with no history of biliary colic in the last month, and no ASA I and II dilatation of bile ducts were included. Three trocars (T) are inserted: T1, 10mm on the umbilicus; T2, 5 mm on the left upper quadrant; and T3, 10 mm on the supra-pubic area above the lower abdominal fold for facilitating the use of a 10-mm 0º lens. Results: Between April and May 2012, 20 patients met the inclusion criteria, 16 had cholelithiasis and 4 had gallbladder polyps. No patient required conversion to traditional laparoscopic surgery, and the operative time did not differ from conventional laparoscopic surgery when compared with patients with similar characteristics operated by the same group of surgeons. There was a rapid adaptation and preference for this new technique. There were no intra-operative or post-surgical complications. Conclusions: This approach is a feasible, safe and effective technique. Surgeons who routinely perform laparoscopic gallbladder surgery using three trocars (two for working and one for the camera) may perform this technique without undergoing more specialized training or using special equipment, and we are able to offer better esthetic results for patients.